As global poverty levels increase, let us not forget period poverty - Janet Michel; Chioma Ginikawa; Margaret Zou; Otridah Kapona; Danielle Agnello; Marcel Tanner (Inishmore Laser Scientific Publishing Ltd, 2023)
In many low- and middle-income countries (LMICs), period poverty is ubiquitous. As global poverty levels rise, period poverty is bound to rise too. The education and empowerment of women and girls particularly in LMICs are at stake. The dignity needed for menstruating people to attend to their menstrual cycle is a need rather than a luxury. Dignity is all we are asking for. Ending period poverty is no rocket science. Scotland has just spearheaded the way, demonstrating to the world, how easily period poverty can be eradicated. We encourage other countries of the world, to follow suit, particularly, governments of low-and middle-income countries. Getting rid of period poverty means getting rid of one system component, holding women and girls back, from contributing and participating fully in the economic system. The world is indeed facing unprecedented challenges, let's not forget a parallel and equally real challenge, period poverty.